EVALUATING THE IMPACT OF WORK-FROM-HOME PRACTICES ON JOB SATISFACTION AND WORK-LIFE BALANCE AMONG IT EMPLOYEES - Rani, Kanchan; Kaur, Kuldeep (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The shift to working from home has changed the nature of work, especially in the information technology (IT) industry. This study looks at how work-from-home policies affect IT professionals in Tricity (Punjab), which consists of Chandigarh, Panchkula, and Mohali, in terms of Work-Life Balance (WLB) and Job Satisfaction (JS). A detailed questionnaire was used to gather information from 460 participants spread over 23 IT companies in the Tri-City area. The relationships between WFH, WLB, JS, and turnover intentions (TI) were examined using structural equation modelling (SEM). The findings show a strong positive correlation between working remotely and both WLB and JS. Furthermore, it was discovered that JS and WLB mediated the association between TI and remote work. The measurement model’s validity and reliability are validated by factor loadings and reliability statistics. The analysis of discriminant validity shows how unique the constructs are. According to the study, IT professionals’ WLB and JS are positively impacted by remote work, which eventually lowers their intentions to leave their jobs. These results highlight how crucial remote work policies are for fostering worker happiness and business success in the IT industry.